PRAGMATIC FUNCTIONS OF MODERN ENGLISH PHRASEOLOGY - ALIMOVA FERUZA ASKARJANOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses Pragmatic functions of the phraseological units of modern English, its history and development paths, as well as different types of phraseological units. One of the most debatable problems in modern phraseology is the problem of functioning of phraseological units (PU). The results of studying the basic pragmatic functions of phraseological units in modern English are provided in this paper. The theoretical background of the research is based on the phrase logical concept introduced by. A. V. Kunin. The research is carried out on the language material extracted from modern lexicographic sources.